Caring Science within Islamic Contexts: A Literature Review - Ismail, Suhartini; Hatthakit, Urai; Chinawong, Tippamas (Department of Nursing, Faculty of Medicine, Diponegoro University, 2015)
Background: Caring is an essence of nursing and many studies enlighten about caring for various populations and settings. Caring science within Islamic contexts has gained more attention from nurses, especially in the area related to cultural and spiritual care.Purpose: The aim of this study was to discuss the concepts of caring science within Islamic contexts. Methods: We extracted 27 articles in both qualitative and quantitative studies, inthe English language, based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. The date and years were limited from January 2008 to 2014 from several databases. Keywordswere ‘caring science’, ‘Islamic caring’, ‘and Islamic Perspectives’ and combined with words of ‘Nursing’, ‘caring’, and ‘care’.Result: There were 4 themes in caring within Islamic context: 1There were 6 themes in caring within Islamic context: 1) theoretical definition of caring; 2) foundation of caring; 3) comparison of caring theories; and 4) caring in Islamic culture; 5) caring practice in Islamic perspectives;and 6) caring outcomesConclusion: In Islamic nursing, caring is based on well-being improvement and healing, and concentration on all domains of nursing care and relationship between different dimensions of human (bio-psycho-social-spiritual dimensions). Within these contexts, a better understanding of the diverse conceptualizations of nursing is needed in order to ensure that nurses across all contexts can provide optimal care.